Fluorescence study of the solvation of fluorescent probes prodan and laurdan in poly(epsilon-caprolactone)-block-poly(ethylene oxide) vesicles in aqueous solutions with tetrahydrofurane - Sachl, Radek; Stepánek, Miroslav; Procházka, Karel; Humpolícková, Jana; Hof, Martin (Langmuir, 2008)
Steady-state and time-resolved fluorescence measurements were used to study the relaxation of the microenvironment of hydrophobic probes 6-propionyl-2-(dimethylamino)naphthalene (prodan) and 6-dodecanoyl-2-(dimethylamino)naphthalene (laurdan) in systems containing vesicles formed by the amphiphilic diblock copolymer poly(epsilon-caprolactone)-block-poly(ethylene oxide) (PCL-PEO) and water/tetrahydrofurane (THF) solvent mixtures. It was found that in case of prodan, both steady-state and time-resolved emission spectra were composed of two subspectra corresponding to the emission of prodan molecules located (i) in fairly rigid (effectively viscous) and hydrophobic domains of the vesicles close to the PCL/PEO interface and (ii) in a more polar and less viscous medium (in the bulk solution). The fraction of the emission from the more polar microenvironment increases with increasing content of THF in the system. Laurdan, in contrast to prodan, appeared to be solubilized preferentially in the hydrophobic domains up to 30 vol % of THF content, and its emission spectra changed only due to swelling of hydrophobic PCL domains by added THF. The study shows that the analysis of the time-resolved emission from a probe distributed in two media is, in principle, possible, but it is quite complex and appreciably less accurate, and the relaxation times are ill-defined averages of several processes. The bimodal or shoulder-containing time-resolved spectra have to be decomposed in pertinent time-resolved subspectra and treated separately. Another important result of the study is a piece of knowledge concerning the motion of the probe with respect to the vesicle. In the studied complex system, not only the relaxation of the solvent and reorganization of polymer segments around the fluorescent headgroup of the probe affect the emission but also a lateral motion of the probe with respect to the nanoparticle within the lifetime of the excited state contributes significantly to the relaxation and to the relatively slow time-resolved Stokes shift.